Healthcare-seeking behaviors for acute respiratory illness in two communities of Java, Indonesia: a cross-sectional survey - Catharina Y. Praptiningsih; Kathryn E. Lafond; Yunita Wahyuningrum; Aaron D. Storms; Amalya Mangiri; Angela D. Iuliano; Gina Samaan; Christiana R. Titaley; Fitra Yelda; Jennifer Kreslake; Douglas Storey; Timothy M. Uyeki (Springer, 2019)
Understanding healthcare-seeking patterns for respiratory illness can help improve estimations of disease burden and inform public health interventions to control acute respiratory disease in Indonesia. The objectives of this study were to describe healthcare-seeking behaviors for respiratory illnesses in one rural and one urban community in Western Java, and to explore the factors that affect care seeking. From February 8, 2012 to March 1, 2012, a survey was conducted in 2520 households in the East Jakarta and Bogor districts to identify reported recent respiratory illnesses, as well as all hospitalizations from the previous 12-month period. We found that 4% (10% of those less than 5 years) of people had respiratory disease resulting in a visit to a healthcare provider in the past 2 weeks; these episodes were most commonly treated at government (33%) or private (44%) clinics. Forty-five people (0.4% of those surveyed) had respiratory hospitalizations in the past year, and just over half of these (24/45, 53%) occurred at a public hospital. Public health programs targeting respiratory disease in this region should account for care at private hospitals and clinics, as well as illnesses that are treated at home, in order to capture the true burden of illness in these communities.